Reduced aquaporin-1 transcript expression in colorectal carcinoma is associated with promoter hypermethylation. Issue 2 (1st February 2019) - Smith, Eric; Tomita, Yoko; Palethorpe, Helen M.; Howell, Stuart; Nakhjavani, Maryam; Townsend, Amanda R.; Price, Timothy J.; Young, Joanne P.; Hardingham, Jennifer E.
ABSTRACT: Aquaporin-1 (AQP1) is a homo-tetrameric transmembrane protein that facilitates rapid movement of water and ions across cell membranes. The clinical significance of AQP1 expression in colorectal carcinoma (CRC) is controversial. The aim of this study was to investigate the prognostic significance of AQP1 transcript expression and the association between expression and promoter methylation in normal colonic mucosa, CRC tissues and cell lines. Analysis of publicly available datasets from The Cancer Genome Atlas revealed that AQP1 expression was significantly decreased in CRC compared to normal mucosa (12.7 versus 33.3 respectively, P < 0.0001). However, expression increased with advanced disease, being significantly higher in stage IV (17.6) compared to either stage I (11.8, P = 0.0039) or II (10.9; P = 0.0023), and in patients with lymph node metastasis compared to those without (13.9 versus 11.3 respectively, P = 0.0023). Elevated expression was associated with decreased overall survival with univariate (Cox Proportional Hazard Ratio 1.60, 95% confidence interval 1.05–2.42, P = 0.028), but not multivariable analysis when considering the confounders stage and age. Analysis of HumanMethylation450 data demonstrated that AQP1 promoter methylation was significantly increased in CRC compared to normal mucosa. Analysis of CRC tissues and cell lines strongly suggested that methylation was associated with decreased expression. BRAF V600E mutation alone did not explain the increase in methylation. In conclusion, AQP1 transcript expression was decreased in CRC compared to normal mucosa, and this was associated with AQP1 promoter hypermethylation. AQP1 transcript expression increased with advanced disease but was not an independent prognostic indicator.